MEASUREMENT OF THE BRANCHING RATIO OF THE DOUBLE DALITZ DECAY K-L-]E(+)E(-)E(+)E(-) AND THE CP PARITY OF THE K-L-MESON - Barr, G; Buchholz, P; Cundy, D; Doble, N; Gatignon, L; Grafstrom, P; Hagelberg, R; Wahl, H; Peach, K; Beier, T; Blumer, H; Coward, D; et al. (Springer-Verlag, 1995)
Data from the NA31 experiment at CERN have been used to measure the branching ratio of the double Dalitz decay of the long-lived neutral kaon. Eight events have been found with negligible background. The measured distribution of the angle between the planes of the two e+e--pairs favours a CP=-1 state for the long-lived neutral kaon. © 1995 Springer-Verlag.